Bibliometric analysis of photodynamic research in bladder cancer: Trends and future directions - Xi Xu; Jinshan Xu; Hongliang Gao; Zhaoyang Sheng; Yang Xu; Shuxiong Zeng; Guanghua Chen; Zhensheng Zhang (Photodiagnosis and Photodynamic Therapy)
Background: Recent years have seen the use of photodynamic technologies concerning the detection and therapy of bladder cancer (BC) due to their rapid development and well-established therapeutic impact. However, a thorough analysis and bibliometric assessment of photodynamic technologies publishing trends in BC has not been completed yet. Methods: Retrieving bibliographies from the Web of Science Core Collection limited the publication date to December 31, 2023, from January 1, 2004. We used VOSviewer (Version 1.6.19) and CiteSpace (Version 6.4 R1) for both statistical and visualization analysis. Results: We selected a total of 870 documents for analysis. The yearly publication findings show notable upward patterns over the last two decades. The Kochi Medical School in Japan was the most productive school, while the USA was the most productive nation. Japanese researcher Inoue Keiji published the highest number of photodynamic -related articles in BC. The most quoted and prolific journals were the Photodynamic Therapy and Photodiagnosis. According to the keyword analysis, the terms ''cystoscopy,'' ''carcinoma in situ,'' ''drug delivery,'' ''follow-up,'' ''hexaminolevulinate,'' and ''impact'' are all relatively recent and hot field. Conclusions: Our investigation produced a bibliometric outcome for the field, potentially opening up new research opportunities. We suggest that future research concentrate on in-situ carcinoma identification, photosensitizer invention, medication delivery enhancement, and photodynamic technology follow-up in BC.